Granulocytic sarcoma: Extramedullary manifestation of chronic myeloproliferative neoplasm in a young African woman - Ajayi A. Ibijola; Abiodun I. Okunlola; Abiodun O. Awe (Elsevier, 2021)
We present a rare case of multiple granulocytic sarcoma in a young African woman in blast phase of chronic myeloproliferative neoplasm. Fine needle aspiration cytology of the sarcoma, peripheral blood film and bone marrow aspiration cytology were consistent with chronic myeloid leukaemia in blast phase. Objective: To present a rare case of multiple granulocytic sarcoma as extramedullary manifestation of chronic myeloproliferative neoplasm in the context of creating awareness about this rare unusual presentation.